Factors Influencing The Incidence of Stunting in Toddlers in The Work Area of Kadudampit Health Center, Sukabumi District - Utami, Rima Novianti (STIKep PPNI Jawa Barat, 2024)
Aims: The purpose of this study was to identify the factors that influence the incidence of stunting in toddlers within the working area of Kadudampit Health Center, Sukabumi District. Methods: This research employed a correlational design with a cross-sectional approach. The population consisted of all mothers with toddlers in Sukamaju Village, within the Kadudampit Health Center working area of Sukabumi District, totaling 362 respondents. A simple random sampling technique was used to select participants. Data analysis was conducted using the chi-square test and logistic regression analysis. Results: There is a significant influence of maternal knowledge, parenting patterns, economic status, maternal education, and exclusive breastfeeding on the incidence of stunting (p < 0.05). Additionally, these factors collectively influence the incidence of stunting. Among these variables, economic status is the most dominant factor affecting stunting, with an odds ratio (OR) value of 13.207. Conclusion: There is a simultaneous influence of maternal knowledge, parenting, economic status, maternal education, and exclusive breastfeeding on the incidence of stunting, with economic status being the most dominant variable affecting stunting.